Discrepancies between registration and publication of randomised controlled trials: an observational study. (9th April 2014) - Walker, Kate F; Stevenson, Graham; Thornton, James G
Summary: Objectives: To determine the consistency between information contained in the registration and publication of randomised controlled trials (RCTs). Design: An observational study of RCTs published between May 2011 and May 2012 in the British Medical Journal ( BMJ ) and the Journal of the American Medical Association ( JAMA ) comparing registry data with publication data. Participants and Settings: Data extracted from published RCTs in BMJ and JAMA. Main outcome measures: Timing of trial registration in relation to completion of trial data collection and publication. Registered versus published primary and secondary outcomes, sample size. Results: We identified 40 RCTs in BMJ and 36 in JAMA . All 36 JAMA trials and 39 (98%) BMJ trials were registered. All registered trials were registered prior to publication. Thirty-two (82%) BMJ trials recorded the date of data completion; of these, in two trials the date of trial registration postdated the registered date of data completion. There were discrepancies between primary outcomes declared in the trial registry information and in the published paper in 18 (47%) BMJ papers and seven (19%) JAMA papers. The original sample size stated in the trial registration was achieved in 24 (60%) BMJ papers and 21 (58%) JAMA papers. Conclusions: Compulsory registration of RCTs is meaningless if the content of registry information is not complete or if discrepancies between registration and publication are not reported. This study demonstrates that discrepancies in primary and secondary outcomes and sample size between trial registration and publication remain commonplace, giving further strength to the World Health Organisation's argument for mandatory completion of a minimum number of compulsory fields.